High-efficiency solar-to-hydrogen systems: Multi-junction CPV cell coupled with solid oxide electrolyzer - Kale, Cihangir; Esen, Hikmet (Pergamon-Elsevier Science Ltd, 2025)
This study investigates the hydrogen production potential of a system integrating concentrated photovoltaic solar cells and solid oxide electrolyzers. Analyses are conducted using a concentrated multi-junction solar cell having an active area of 10x10 mm2, operating at different concentration ratios (250X, 500X, 1000X). The concentrated photovoltaic solar cell reaches a steady-state temperature of approximately 100 degrees C at a concentration ratio of 500X, demonstrating effective thermal management of concentrated photovoltaic under real outdoor conditions. The electrical production efficiency of the optical system is determined to be 34.26%, while the solar-to-hydrogen efficiency of the integrated system is calculated to be 35.25%, assuming that the thermal load required for the operation of the solid oxide electrolyzer is supplied by waste heat. This efficiency value is found to be approximately three times higher than the hydrogen production efficiencies of polymer electrolyte membrane and alkaline electrolyzers used in combination with Si-based conventional solar cells. These findings suggest that hydrogen production utilizing concentrated photovoltaic solar cells and solid oxide electrolyzers provides a promising alternative to conventional methods with significantly higher efficiencies.
Keywords: Hydrogen production; Renewable energy; Multi-junction solar cell; Solid oxide electrolyzer